Objectively Measured Physical Activity Is Associated With Body Composition and Metabolic Profiles of Pacific and New Zealand European Women With Different Metabolic Disease Risks - Slater, Joanne; Kruger, Rozanne; Douwes, Jeroen; O’Brien, Wendy J.; Corbin, Marine; Miles-Chan, Jennifer L.; Breier, Bernhard H. (Frontiers in Physiology, 2021)
Objective: To assess associations between physical activity (PA), body composition, and biomarkers of metabolic health in Pacific and New Zealand European (NZE) women who are known to have different metabolic disease risks. Methods: Pacific (n=142) or NZE (n=162) women aged 18-45 years with a self-reported body mass index (BMI) of either 18.5-25.0 kg·m-2 or ≥30.0 kg·m-2 were recruited and subsequently stratified as either low (<35%) or high (≥35%) BF%, with approximately half of each group in either category. Seven-day accelerometery was used to assess PA levels. Fasting blood was analysed for biomarkers of metabolic health, and whole body dual-energy x-ray absorptiometry was used to estimate body composition. Results: Mean moderate-to-vigorous physical activity (MVPA; min·day-1) levels differed between BF% (p<0.05) and ethnic (p<0.05) groups: Pacific high- 19.1 (SD 15.2) and low-BF% 26.3 (SD 15.6) and NZE high- 30.5 (SD 19.1) and low-BF% 39.1 (SD 18.4). On average Pacific women in the low-BF% group engaged in significantly less total PA when compared to NZE women in the low-BF% group (133 cpm); no ethnic difference in mean total PA (cpm) between high-BF% groups were observed: Pacific high- 607 (SD 185) and low-BF% 598 (SD 168) and NZE high- 674 (SD 210) and low-BF% 731 (SD 179). Multiple linear regression analysis controlling for age and deprivation showed a significant inverse association between increasing total PA and fasting plasma insulin among Pacific women; every 100 cpm increase in total PA was associated with a 9% decrease in fasting plasma insulin; no significant association was observed in NZE women. For both Pacific and NZE women, there was an 8% reduction in fasting plasma insulin for every 10-minute increase in MVPA (p≤0.05). Conclusions: Increases in total PA and MVPA are associated with lower fasting plasma insulin, thus indicating a reduction in metabolic disease risk. Importantly, compared to NZE, the impact of increased total PA on fasting insulin may be greater in Pacific women. Considering Pacific women are a high metabolic disease risk population, these pre-clinical responses to PA may be important in this population; indicating promotion of PA in Pacific women should remain a priority.